A review on the methods to evaluate crowd contributions in crowdsourcing applications - Aris H.; Azizan A. (Springer, 2023)
Computation theory; Intelligent computing; Surveying; Automated evaluation; Evaluation method; Evaluation methods; Expert judgement; Grounded theory; New evaluation methods; Systematic Review; Crowdsourcing